Nutrition and upper gastrointestinal cancers: An overview of current understandings. (August 2022) - Kayamba, Violet
Abstract: Upper gastrointestinal (UGI) cancers are among the most common cancers in the world, four of them being among the top eight causes of cancer related mortality. Included among UGI cancers are oesophageal, gastric, liver, biliary, pancreatic and small intestinal cancers. Despite more than half a century of well designed epidemiological (large cohort and case-control studies) and a limited number of experimental studies into the role of nutrition on UGI cancer, there is much inconsistency in the findings. Studies have reported significant associations of various food types and UGI cancers, but there are issues with reproducibility. Over the years, numerous meta-analyses have been conducted in an attempt to harmonize available data. On the whole, it is well accepted that fruit and vegetables reduce UGI cancer risk, while processed foods increase the risk. The role of antioxidants in protecting against UGI carcinogenesis is of great interest, but controversial. There is evidence that specific diets, such the Mediterranean or Okinawa, are associated with reduced cancer risk at a population level, but it is less clear if adopting them reduces risk in otherwise high-risk locations. In this review, I will discuss some of the available literature from selected original publications, systematic reviews and meta-analyses on the influence of diet on UGI cancers. I will also provide a brief overview of future directions that have the potential to provide specific evidence on how diet could be modified to reduce the growing global burden of UGI cancers.